Practice, instruction and skill acquisition in football - Williams, M. (7th World Congress on Science and Football (WCSF), 2011, 2011)
In this presentation an overview is provided of contemporary research focusing on the role of practice and instruction in developing elite players across the different codes of football. Initially, recent empirical research involving the deliberate practice theoretical framework is reviewed in an attempt to outline the typical developmental history profiles of elite athletes in the football codes. The key milestones (e.g., the age that players commence participation and specialise in the sport) are identified as well as the amount and type of practice activities in which they have engaged during their career in the sport, as well as in other athletic activities. The main differences in practice history profiles between expert and less expert players are highlighted and implications for talent search and development discussed. Next, an overview is provided of theoretical principles emerging from the discipline of motor learning related to identifying those factors that promote effective practice and instruction. The types of practice activities and instructional approaches that are known to promote learning are presented and these are discussed in light of recent empirical work that has presented time-use analyses of the activities that players actually participate in during formal, coach-led practice sessions. The evidence presented suggests that there exists a substantial divide between the existing practices that are employed to promote the development of elite footballers in the field and the principles underpinning the science of learning. Some suggestions are made as to how this theory-practice divide may be bridged and how the use of practice time may be optimised so as to best promote efficient and effective skill learning in future generations of elite players in football.